Solid Ground : Increasing Community Resilience Through Improved Land Administration and Geospatial Information Systems - World Bank (World Bank, Washington, DC, 2020)
Countries struck by equally powerful disaster events are affected differently in terms of thedevastation caused, the number of casualties, persons displaced, impact on livelihoods, andthe pace of reconstruction and recovery. Some communities, cities, and populations proveto be more resilient than others when faced with disasters. The ability of land and people-to-land relationships to recover after hazard events requires reliable administration systems and authoritative geospatial information. Land administration systems provide security of tenure; control inappropriate land uses; ensure safe construction of buildings and infrastructure; and undertake land valuation for finance, taxation, and compensation. Underpinning effective land administration is accurate geospatial information. An authoritative geospatial information system comprises a series of fundamental databases including addresses, buildings, settlements, elevation and depth, functional areas, geographical names, geology and soils, land cover and land use, landparcels, orthoimagery, physical infrastructure, population distribution, transport and utilitynetworks, water, and a geographic reference framework. Land administration systems and geospatial information play key roles in the planning, monitoring, and implementation of responses before, during, and after disasters. With disaster events around the world increasing in frequency and severity, better access to land and geospatial information is critical to disaster risk management activities, from disaster preparedness and risk mitigation through recovery and reconstruction.Several key initiatives aimed at building resilience to disasters have emerged in recentdecades, including the 2030 Agenda for Sustainable Development, the Hyogo Frameworkfor Action, and the Sendai Framework for Disaster Risk Reduction. The Integrated GeospatialInformation Framework (IGIF), released by the UN and the World Bank, complements theHyogo and Sendai agendas calling for globally coordinated actions in new geospatial dataacquisition and integration. These global initiatives highlight the positive effects thateffective land administration and geospatial information systems can have.